Testing the inhibitory cascade model in a recent human sample. Issue 5 (5th July 2021) - Bermúdez de Castro, José María; Modesto‐Mata, Mario; García‐Campos, Cecilia; Sarmiento, Susana; Martín‐Francés, Laura; Martínez de Pinillos, Marina; Martinón‐Torres, María
Abstract: The Inhibitory Cascade Model was proposed by Kavanagh and colleagues (Nature, 449, 427–433 [2007]) after their experimental studies on the dental development of murine rodent species. These authors described an activator–inhibitor mechanism that has been employed to predict evolutionary size patterns of mammalian teeth, including hominins. In the present study, we measured the crown area of the three lower permanent molars (M1, M2, and M3) of a large recent modern human sample of male and female individuals from a collection preserved at the Institute of Anthropology of the University of Coimbra (Portugal). The main aim of the present study is to test if the size molar patterns observed in this human sample fits the Inhibitory Cascade Model. For this purpose, we first measured the crown area in those individuals preserving the complete molar series. Measurements were taken in photographs, using a planimeter and following well‐tested techniques used in previous works. We then plot the M3 /M1 and M2 /M1  size ratios. Our results show that the premise of the Inhibitory Cascade Model, according to which the average of the crown area of M2 is approximately one‐third of the sum of the crown area of the three molars, is fulfilled. However, our results also show that the individual values of a significant number of males and females are out of the 95% confidence interval predicted by the Inhibitory Cascade Model in rodents. As a result, the present analyses suggest that neither the sample of males, nor that of females, nor the pooled sample fits the Inhibitory Cascade Model. It is important to notice that, although this model has been successfully tested in a large number of current human populations, to the best of our knowledge this is the first study in which individual data have been obtained in a recent human population rather than using the average of the sample. Our results evince that, at the individual level, some factors not yet known could interfere with this model masking the modulation of the size on the molar series in modern humans. We suggest that the considerable delay in the onset of M3 formation in modern humans could be related to a weakening of the possible activation/inhibition process for this tooth. Finally, and in support of our conclusions, we have checked that the absolute and relative size of M1 and M2 is not related to the M3 agenesis in our sample. In line with other studies in primates, our results do not support the Inhibitory Cascade Model in a recent human sample. Further research is needed to better understand the genetic basis of this mechanism and its relationship to the phenotype. In this way, we may be able to find out which evolutionary changes may be responsible for the deviations observed in many species, including Homo sapiens . Abstract : In the present study, we measured the crown area of the three lower permanent molars (M1, M2, and M3) of a large recent modern human sample of male and female individuals from a collection preserved at the Institute of Anthropology of the University of Coimbra (Portugal). The main aim of the present study is to test if the size molar patterns observed in this human sample fits the Inhibitory Cascade Model. In line with other studies in primates, our results do not support this model.